2020
DOI: 10.1186/s41235-019-0199-7
|View full text |Cite
|
Sign up to set email alerts
|

Are subjective sleepiness and sleep quality related to prospective memory?

Abstract: Event-based prospective memory (PM) involves carrying out intentions when specific events occur and is ubiquitous in everyday life. It consists of a prospective component (remembering that something must be done) and a retrospective component (remembering what must be done and when). Subjective sleep-related variables may be related to PM performance and an attention-demanding prospective component. In two studies, the relationship of subjective sleepiness and subjective sleep quality with both PM components w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 157 publications
3
9
0
Order By: Relevance
“…On the contrary, they observed a sleep-facilitating effect on spontaneous retrieval processes. This pattern of results points out that the topic of the relationship between sleep and PM is still under discussion, as recently demonstrated by Böhm and colleagues [21], who failed to detect a significant association between sleep and PM. Within the research agenda of their study, Leong et al [20] wrote that "while slow-wave sleep plays a key role in PM in young adults, this relationship may change with age.…”
Section: Introductionsupporting
confidence: 74%
“…On the contrary, they observed a sleep-facilitating effect on spontaneous retrieval processes. This pattern of results points out that the topic of the relationship between sleep and PM is still under discussion, as recently demonstrated by Böhm and colleagues [21], who failed to detect a significant association between sleep and PM. Within the research agenda of their study, Leong et al [20] wrote that "while slow-wave sleep plays a key role in PM in young adults, this relationship may change with age.…”
Section: Introductionsupporting
confidence: 74%
“…Moreover, it is still not currently known which of the three sleep pillars could be more strongly associated with PM. Overall, this pattern of results highlights the fact that the role of low sleep quality in the impairment of PM performance is still a matter of debate, as also shown by a recent study [15] that failed to find a significant association between sleep and PM and which is not included in the above-mentioned systematic review and meta-analysis [14]. Confirming that the role of low sleep quality in the impairment of PM should still be clarified, a recent study of our research group [16] showed, in a large healthy lifespan sample, that sleep quality, quantity, and timing do not play a predictive role in PM performance contrary to aging that was per se associated with its worsening.…”
Section: Introductionsupporting
confidence: 82%
“…The main aim of the present study was to explore the potential role of sleep quality and amount in PM, which is currently still a matter of debate [ 14 , 15 , 16 ]. To this end, we carried out a retrospective naturalistic study in which we examined different clinical populations with a primary sleep disorder or comorbid low sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…The model was validated for nonfocal PM tasks (Horn et al, 2011 ; Rummel et al, 2011 ; Smith & Bayen, 2004 ) and has been applied frequently (Arnold & Bayen, 2019 ; Arnold, Bayen, & Böhm, 2015 ; Arnold, Bayen, & Smith, 2015 ; Böhm et al, 2020a ; Pavawalla et al, 2012 ; Schnitzspahn et al, 2012 ; Smith et al, 2010 ; Smith et al, 2014 ; Smith & Bayen, 2005 , 2006 ; Walter & Bayen, 2016 ; Wesslein et al, 2014 ; Zhang et al, 2017 ).…”
Section: Analyses and Resultsmentioning
confidence: 99%
“…In one of our previous studies (Böhm et al, 2020a), participants performed a PM task embedded in an ongoing color-matching task in three consecutive blocks, each with new PM target words. In unpublished analyses of these data (Böhm et al, 2020b), we found that even three consecutive blocks of PM tasks did not induce interference effects. On the contrary, PM performance was even slightly better on the later PM blocks.…”
Section: Discussionmentioning
confidence: 99%